Solvent and Substituent Effect on Selectivity of Triphenylether-Based Ionophores: A Voltammetric Study - Susheel K. Mittal; Shivali Gupta; Manmohan Chhibber (C, 2021)
The past two decades have seen considerable attention given to chemical sensing due to its quick, reproducible, and accurate results. These are extensively used for the detection of cations and anions in different environmental matrices. Organic-molecule-based sensors have proved to be a great promising tool in determining target species. This communication demonstrates the use of triphenylether derivatives (L1–L4) as receptors for the sensing of cations and anions, using voltammetry as a sensing tool. The effect of the oxidative/reductive nature of the ionophores and, hence, their selectivity behavior was studied in MeCN and MeOH solvents. Three receptors (L2–L4) responded selectively towards cyanide ions following the intramolecular charge-transfer mechanism, while sensing in the case of L1 was not studied because it lacked a proper cavity size.